2020
DOI: 10.2174/1875318302010010060
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cotinine as a Biomarker of Cigarette Smoke Exposure: A Method to Differentiate Among Active, Second-Hand, and Non-Smoker Circumstances

Abstract: Objective: To review the literature on the use of urinary cotinine as a biological marker of cigarette smoke exposure. Methods: Narrative review of original and review articles on the topic of interest, published in Portuguese or English by June 2018, and selected in the following online databases: PubMed and Virtual Health Library (VHL). Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Urinary cotinine levels can be used to differentiate between smokers, passive smokers, and non-smokers. 18 However, due to differences in the technique for measuring urinary cotinine levels, to the best of the authors' knowledge, no fixed cut-off point is generally accepted to distinguish the three categories above. The consistent results showed that passive smokers (recipients of SHS and THS exposure from smokers) have significantly higher urinary cotinine levels than non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary cotinine levels can be used to differentiate between smokers, passive smokers, and non-smokers. 18 However, due to differences in the technique for measuring urinary cotinine levels, to the best of the authors' knowledge, no fixed cut-off point is generally accepted to distinguish the three categories above. The consistent results showed that passive smokers (recipients of SHS and THS exposure from smokers) have significantly higher urinary cotinine levels than non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, urine concentrations of cotinine possess four- to six folds the average concentration than that of saliva or blood. Accordingly, urine can be considered a noninvasive, highly sensitive matrix to detect even minimal concentrations caused by tobacco smoke exposure [ 31 ]. The number of cigarettes consumed by the smoker was found to have an association with the cotinine mean value in the urine of passive smokers [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study revealed increased susceptibility to HSPM in children subjected to household smoking where limited impact of smoking form and pattern has been identified to affect the distribution of HSPM. Hypomineralization of the second primary molar (HSPM) describes a qualitative defect affecting tooth enamel that appears during development as well as demarcated opacity with possible enamel breakdown affecting one- to four-primary second molars [ 31 ]. The affected enamel was found to be porous and more liable to break down soon post-tooth eruption into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…KA0930, Abnova, Taiwan), as described previously. 17 Ten microliters of each standard, control, or sample was pipetted into 96-well plates in duplicate by using a repeating pipette (Multipette, Eppendorf, Hamburg, Germany). Then, 100 µL of the enzyme conjugate was added to each well.…”
Section: Measurement Of Cotinine In the Urinementioning
confidence: 99%